Neurophysiological correlates of tactile width discrimination in humans - Pais-Vieira, Carla; Allahdad, Mehrab K.; Perrotta, André; Peres, André S.; Kunicki, Carolina; Aguiar, Mafalda; Oliveira, Manuel; Pais-Vieira, Miguel (Frontiers in Human Neuroscience, 2023)
Introduction Tactile information processing requires the integration of sensory, motor, and cognitive information. Width discrimination has been extensively studied in rodents, but not in humans. Methods Here, we describe Electroencephalography (EEG) signals in humans performing a tactile width discrimination task. The first goal of this study was to describe changes in neural activity occurring during the discrimination and the response periods. The second goal was to relate specific changes in neural activity to the performance in the task. Results Comparison of changes in power between two different periods of the task, corresponding to the discrimination of the tactile stimulus and the motor response, revealed the engagement of an asymmetrical network associated with fronto-temporo-parieto-occipital electrodes and across multiple frequency bands. Analysis of ratios of higher [Ratio 1: (0.5–20 Hz)/(0.5–45 Hz)] or lower frequencies [Ratio 2: (0.5–4.5 Hz)/(0.5–9 Hz)], during the discrimination period revealed that activity recorded from frontal-parietal electrodes was correlated to tactile width discrimination performance between-subjects, independently of task difficulty. Meanwhile, the dynamics in parieto-occipital electrodes were correlated to the changes in performance within-subjects (i.e., between the first and the second blocks) independently of task difficulty. In addition, analysis of information transfer, using Granger causality, further demonstrated that improvements in performance between blocks were characterized by an overall reduction in information transfer to the ipsilateral parietal electrode (P4) and an increase in information transfer to the contralateral parietal electrode (P3). Discussion The main finding of this study is that fronto-parietal electrodes encoded between-subjects’ performances while parieto-occipital electrodes encoded within-subjects’ performances, supporting the notion that tactile width discrimination processing is associated with a complex asymmetrical network involving fronto-parieto-occipital electrodes.